2018
DOI: 10.5194/hess-22-6519-2018
|View full text |Cite
|
Sign up to set email alerts
|

The probability distribution of daily precipitation at the point and catchment scales in the United States

Abstract: Abstract. Choosing a probability distribution to represent daily precipitation depths is important for precipitation frequency analysis, stochastic precipitation modeling and in climate trend assessments. Early studies identified the two-parameter gamma (G2) distribution as a suitable distribution for wet-day precipitation based on the traditional goodness-of-fit tests. Here, probability plot correlation coefficients and L-moment diagrams are used to examine distributional alternatives for the wet-day series o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 38 publications
(51 reference statements)
4
35
0
Order By: Relevance
“…Therefore, KAP is the best distribution model among the employed distributions for QDM to bias-correct the simulated precipitation in South Korea. These results are consistent with the analysis results of the probability distribution for daily precipitation in the United States [20]. They report that KAP is the best distribution for modeling the daily precipitation on a wet day.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, KAP is the best distribution model among the employed distributions for QDM to bias-correct the simulated precipitation in South Korea. These results are consistent with the analysis results of the probability distribution for daily precipitation in the United States [20]. They report that KAP is the best distribution for modeling the daily precipitation on a wet day.…”
Section: Discussionsupporting
confidence: 90%
“…On the basis of the results, the mixed exponential distribution showed the best fit for the data followed by the gamma and exponential distributions, respectively. Ye, Hanson, Ding, Wang, and Vogel (2018) evaluated the performance of 15 distributions in 237 rainfall gauge stations in the United States. The results indicated that the four-parameter kappa distribution showed the best performance to describe the occurrence of daily rainfall in the rainfall gauge stations.…”
mentioning
confidence: 99%
“…Therefore, assessing the applicability of CDFs with different structures is necessary to provide more accurate information on rainfall. In practice, precipitation is simulated using the gamma distribution that in most cases is able to adequately estimate low and moderate rainfall due to its flexibility (Kist & Virgens Filho, 2015;Papalexiou, Koutsoyiannis, & Makropoulos, 2013;Ye et al, 2018;Yoo, Jung, & Kim, 2005). However, the gamma distribution may not be adequate in cases of extreme precipitation values, as magnitude and frequency are often underestimated (Allard & Bourotte, 2015;Kleiber, Katz, & Rajagopalan, 2012).…”
mentioning
confidence: 99%
“…Each distribution has different parameters, and they can all be conveniently computed and parameterized for series. Since the extremes of water systems are often needed to determine the infrastructure design and management plans, improving the prediction using the most reasonable distribution as a model can greatly improve water management practices [26].Second, we will evaluate the non-stationary statistics for hydrological extremes. One example of a non-stationary statistic is the Hurst exponent, first developed to quantify the long-term persistence of water storage of reservoirs by Hurst [27].…”
mentioning
confidence: 99%
“…Each distribution has different parameters, and they can all be conveniently computed and parameterized for series. Since the extremes of water systems are often needed to determine the infrastructure design and management plans, improving the prediction using the most reasonable distribution as a model can greatly improve water management practices [26].…”
mentioning
confidence: 99%